High velocity impact response of carbon/epoxy composite laminates at cryogenic temperatures. (May 2023) - Pernas-Sánchez, J.; García-Rodríguez, S.M.; Artero-Guerrero, J.A.; López-Puente, J.; Costa, J.
Abstract: Composite laminates are subjected to cryogenic temperatures in exposed aircraft structures during flight or in cryogenic tanks. The combination of cryogenic temperatures and high velocity impacts represents a threat to their integrity. This work investigates the behavior of carbon–epoxy laminates under high velocity impacts (from 70 to 500 m/s) at room and cryogenic (-150 °C) temperatures and under two different plate orientations with respect to the projectile direction. The damage pattern of impacted specimens at low temperature, revealed by C-scan and X-ray tomography, exhibits a higher density of fiber breaks and shear matrix cracks which do not translate to a larger projected damaged area. The experimental analysis through interlaminar shear strength tests and the calculation of ply thermal stresses exclude the association of this particular pattern to damage mechanisms induced during the temperature decrease.